Molecular characterization of porcine reproductive and respiratory syndrome virus identified in 2021 from Nepal - Prajapati, Meera; Aryal, Manita; Li, Yanmin; Zhang, Zhidong; Acharya, Madhav Prasad; Clive, Stephanie; Frossard, Jean-Pierre (Frontiers in Veterinary Science, 2024)
Porcine reproductive and respiratory syndrome (PRRS), an important viral disease of swine caused by PRRS virus (PRRSV) was first confirmed in Nepal in 2013. Since then, the virus has spread throughout the country and has now become endemic affecting the pig production nationally. However, molecular characterization of circulating strains has not been done in Nepal yet. In the present study, serum samples were collected from outbreak areas of different districts of Nepal and samples positive for PRRSV by ELISA were sent to Animal and Plant Health Agency (APHA), United Kingdom for sequence analysis. Out of 35 samples that were sent to APHA, only one sample was found positive by PCR and subjected to sequence analysis based on ORF 5, ORF 7 and Nsp2. The results from the phylogenetic analysis demonstrated that the PRRSV strain belongs toPRRSV-2 and lineage 8 strain. The sequences from the Nepalese PRRSV strain revealed a high degree of similarity with the strains isolated from India, China and Vietnam, with the closest genetic relatedness to the Indian isolates from 2020 and 2018. This is the first study on molecular characterization of PRRS virus circulating in Nepal. Further studies on strains circulating in Nepal are very essential to understand the virus diversity, its spread and evolution.